The history of the transport museum of Mutare from 1954-2014 - Muyambo, Gracious Tinashe (Midlands State University, 2017)
This research is a study on the history of the Mutare Museum which was opened to the public in 1964 but this study focus from its humble beginnings from 1954 up to the contemporary period. The research shows the success and failures of the museum throughout its existence. Through an analysis of interviews and oral sources the research presents the chronological summary of the museum. The establishment of the museum was first established as private entity by the colonialist but was later in the 1970s declared as a public institute, therefore the study aims at show casing how that information is of importance as much is being left out as a means of removing traces of the colonial masters in Zimbabwean museums. Throughout its existence the museum faced so many challenges as exchanging of power was experienced over and over again. It can be noted that this led to the focus of the museum being changed in the 1970s as the whites placed the museum under centralization programme. This programme led to the museum’s focus being transport and antiquities. However, the advent of independence led to the redirecting of the aims of the museum as the museum is being changed to the museum of the people with all indigenous people and cultures of the Manicaland province included. This however has been a major challenge as the museum is failing to come about it due to lack of funds and general economic hardships that the country has passed trough in the recent years. Due to independence many scholars have debated that the museum’s history of the colonial period should be removed but this research aims at justifying that removing the colonial traces in the museum will only produce an imbalance history to a larger extend as one cannot talk of its existence without its origins.